The Evolution of the Violin from Classical to Electric Form (Journal of Namibian Studies : History Politics Culture, 2023)
This research consists of four chapters. The first chapter identifies the research problem, as modern technology has become an integral part of our daily lives in contemporary societies. Its indispensable nature lies in the numerous and easily accessible opportunities it provides us, aiming to achieve the best results. Among these modern technologies, contemporary electronic instrument manufacturing has prominently emerged in various musical instrument families, such as the violin, oud, qanun, and electronic guitar. In this study, we will discuss the classical (acoustic) violin and its contemporary electronic counterpart, explaining the differences in manufacturing and performance capabilities between the two instruments.The researcher then established the objectives of the study, which aim to explore the evolution of the violin from its classical form to its electronic form. Furthermore, the researcher set the boundaries of the study.In the second chapter, the researcher discusses the classical violin, its form, and performance specifications.The third chapter delves into the research methodology, research community, research sample, research instrument, and the analysis focused on the electric violin, its form, specifications, and performance capabilities. The fourth chapter presents the researcher's findings, conclusions, recommendations, and proposals.The research concludes with a list of sources and references.